Transparent antistatic protective film and preparation method thereof
By using a one-dimensional high aspect ratio silver-plated nanowire and polythiophene antistatic layer in the antistatic protective film, the problems of unstable antistatic performance and low optical transmittance in the prior art are solved, and the problem of instability in the antistatic performance and low optical transmittance in the prior art is achieved. It has high efficiency and low cost anti-static protection effect, suitable for industrial production.
Patent Information
- Application Number
- CN202411277485.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-12
- Publication Date
- 2024-12-13
AI Technical Summary
The existing antistatic protective films have problems in electronic products with unstable antistatic properties, low optical transmittance, high cost, complex process and serious pollution. Especially after adding conductive fillers to functional coatings, they are prone to curing problems. It cannot meet the requirements of industrial production.
One-dimensional high aspect ratio silver-plated nanowires are used as conductive filler to improve their compatibility with the matrix and dispersion stability through chemical modification. Polythiophene antistatic layer and silver-plated nanowire transparent antistatic functional layer are used. The double-layer structure forms an excellent conductive network, avoiding the impact on optical transmittance and reducing the amount of conductive filler added.
It achieves high optical transmittance (up to 90%), excellent antistatic properties, reduces costs, and extends service life. It is suitable for large-scale production and avoids the problem of functional coating curing.
Smart Images

Figure CN119119548A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of composite film materials, and in particular relates to a transparent antistatic protective film and a preparation method thereof. Background Art
[0002] With the rapid development of the electronics industry, electronic products have gradually become indispensable necessities. Static electricity is a phenomenon in which contact friction causes the charge of an object to accumulate. Many electronic products will generate static electricity during movement and use. Static electricity accumulation can lead to discharge, product short circuit, etc., and even cause safety accidents such as fire and explosion, which will seriously affect the normal use of electronic products and create huge risks and hazards. At present, in the electronics industry, most protective films are attached to the surface of electronic products to play an anti-static role and avoid the impact of static electricity on electronic products.
[0003] Most of the existing antistatic protective films are obtained by two methods: one is to directly add conductive fillers to the functional coating, and the other is to apply an ordinary antistatic layer between the functional coating and the substrate, such as graphite metal grid, silane antistatic coating, conductive polymer material, etc. Among them, adding conductive fillers to the functional coating will make the performance of the obtained functional coating unstable due to the influence of the properties of the conductive fillers themselves and the amount of addition; and applying an ordinary antistatic layer between the functional coating and the substrate will cause the coating to have a significant decrease in light transmittance, insufficient resistance, and the antistatic effect will gradually fade over time. High cost and other problems will not only affect the use of electronic products, but also have poor antistatic effect. In particular, when the functional coating is a silicone pressure-sensitive adhesive coating with a platinum catalytic system, the existing antistatic coating will "poison" the silicone, thereby affecting the curing of the functional coating and the molding and quality of the product. In addition, the antistatic release film disclosed in the prior art is an antistatic liquid of a polythiophene system coated in a substrate and a release agent. Polythiophene has a small energy gap but a high oxidation doping potential, so its oxidation state is very unstable in the air and will be quickly reduced to an intrinsic state. Therefore, the antistatic performance of the obtained antistatic release film is greatly reduced over time due to the reduction of the polythiophene system, and cannot meet the requirements of industrial production and use.
[0004] In order to achieve the preparation of a transparent antistatic protective film with excellent stable antistatic performance and high optical transmittance, patent CN16970205A publicly reported that graphene was used as the main conductive filler, carboxymethyl cellulose alkali metal salt was used to improve the graphene dispersibility and the viscosity of the dispersion, sulfonic acid-doped polyaniline was used to compound it, and then an aqueous binder was added to prepare a composite antistatic protective film. However, the modification of functionalized graphene and the doping of polyaniline in the antistatic protective film prepared by this process have a long production cycle, a complex process, and are not conducive to large-scale production, and the optical transmittance of the prepared antistatic protective film is poor (<70%). Patent CN114773717B publicly reported that one-dimensional chain antimony tin oxide and silver nanowires were first surface-modified with a vinyl-containing silane coupling agent, and then chemically grafted with oil-based palmitamide, and added as conductive fillers to a polyethylene substrate to prepare an antistatic protective film. However, the surface modification and chemical grafting of chain-like antimony tin oxide and silver nanowires in this process require a large amount of acid and alkali for pretreatment. The waste liquid after treatment cannot be recycled, which causes serious pollution. The surface modification and chemical grafting process are complicated and tedious, and the reaction cycle is long. The surface resistance of the prepared antistatic protective film is high (~10 7 Therefore, it is necessary to develop a method for preparing a transparent antistatic protective film with excellent antistatic performance, high optical transmittance, low cost and large-scale production. Summary of the invention
[0005] In view of the deficiencies in the prior art, the present invention provides a transparent antistatic protective film and a preparation method thereof, which adopts one-dimensional high aspect ratio silver-plated nanowires. Due to its good conductivity, stable structure, easy formation of a conductive network, easy material preparation, simple production process and low cost, the antistatic function can be achieved at a relatively low filling amount (<3%), greatly reducing the percolation threshold of the conductive filler, effectively avoiding the influence on the optical transmittance of the film, and greatly improving the optical transmittance of the antistatic protective film (reaching 90%); in addition, by chemically modifying the one-dimensional high aspect ratio silver-plated nanowires, the compatibility of the conductive filler with the matrix and the dispersion stability in the matrix are greatly improved; the silver-plated nanowires have little effect on the functional coating, especially will not cause the "poisoning" of the silicone pressure-sensitive adhesive of the platinum catalytic system or the silicone oil release agent of the platinum catalytic system, thereby not causing the pressure-sensitive adhesive or the release agent to not cure or not completely cure, solving the problem that the curing of the functional coating is affected after the conductive filler is added, enhancing the environmental tolerance of the antistatic protective film, greatly extending the service life of the antistatic protective film, reducing the production cost, and facilitating large-scale production.
[0006] A transparent antistatic protective film, specifically comprising a substrate and a coating attached thereon, wherein the coating comprises a polythiophene antistatic layer and a silver-plated nanowire transparent antistatic functional coating;
[0007] A polythiophene antistatic layer and a silver-plated nanowire transparent antistatic functional coating are sequentially arranged on one surface of the substrate;
[0008] The thickness of the transparent antistatic protective film is 50 to 200 μm, the thickness of the substrate is 10 to 200 μm; the surface resistance of the polythiophene antistatic layer is 10 5 ~10 7 Ω, thickness is 0.05~50μm; the surface resistance of the silver-plated nanowire transparent antistatic functional coating is 10 4 ~10 8 Ω, thickness is 0.1~100μm.
[0009] The material of the substrate is selected from one of PET, PI, PE, PP, and PVC films; the polythiophene antistatic layer is prepared by coating a polythiophene antistatic liquid on the surface of the substrate; and the silver-plated nanowire transparent antistatic functional coating is prepared by mixing a silver-plated nanowire dispersion with a polymer matrix and ultrasonically dispersing the mixture, and then coating the mixture on the surface of the polythiophene antistatic layer.
[0010] The preparation method of the polythiophene antistatic liquid is as follows: adding polythiophene to a mixed solution of ethanol and water, and stirring the mixture to obtain the antistatic liquid; wherein the volume ratio of polythiophene to ethanol and water is 1:(1-3):(1-3), and the polythiophene and ethanol are analytically pure;
[0011] The polymer matrix is selected from one of a release agent, a pressure-sensitive adhesive and a hardening resin, wherein the release agent is a silicone oil release agent, the pressure-sensitive adhesive is selected from one of an organic silicone pressure-sensitive adhesive, an acrylate pressure-sensitive adhesive and a rubber pressure-sensitive adhesive, and the hardening resin is selected from one of an acrylic resin, a polyurethane resin and an epoxy resin;
[0012] The silicone oil release agent is a silicone oil release agent of a platinum catalytic system, and the pressure-sensitive adhesive is an organic silicone pressure-sensitive adhesive of a platinum catalytic system;
[0013] The preparation method of the silver-plated nanowire dispersion is as follows: adding the silver-plated nanowires into an organic solvent, adding a silane coupling agent for modification, and stirring to obtain the dispersion;
[0014] The addition amount of the silver-plated nanowire dispersion accounts for 1% to 20% of the total weight of the polymer matrix, the addition amount of the silver-plated nanowires accounts for 0.5% to 10.0% of the total weight of the polymer matrix, and the addition amount of the silane coupling agent accounts for 0.1% to 0.5% of the total weight of the silver-plated nanowire dispersion.
[0015] The silver-plated nanowires are specifically one-dimensional high aspect ratio silver-plated nanowires, selected from one or more of silver-plated nickel nanowires, silver-plated carbon nanotubes, silver-plated tin dioxide nanowires, and silver-plated zinc oxide nanowires, all of which are prepared by chemical plating process. When multiple types of silver-plated nanowires are selected, the multiple types are in any proportion.
[0016] The silver-plated nickel nanowire has a diameter of 1 to 100 nm and a length of 0.5 to 100 μm, the silver-plated carbon nanotube has a diameter of 5 to 20 nm and a length of 5 to 50 μm, the silver-plated tin dioxide nanowire has a diameter of 20 to 100 nm and a length of 10 to 50 μm, and the silver-plated zinc oxide nanowire has a diameter of 10 to 50 μm and a length of 20 to 50 μm;
[0017] The organic solvent is selected from at least two of ethanol, isopropanol, ethyl acetate and cyclohexane, and the organic solvents are in any proportion. The purity of the organic solvent is analytical grade.
[0018] The silane coupling agent is selected from one or a combination of two or more of γ-glycidoxypropyltrimethoxysilane, γ-glycidoxypropylmethyldiethoxysilane, N-(2-aminoethyl-3-aminopropyl)methyldimethoxysilane, n-octyltriethoxysilane, γ-aminopropyltriethoxysilane, γ-methacryloxypropyltrimethoxysilane, 3-glycidyloxypropyltrimethoxysilane, N-β (aminoethyl)γ-aminopropyltrimethoxysilane and N-β (aminoethyl)γ-aminopropylmethyldimethoxysilane, and the purity of the silane coupling agent is analytically pure; when the silane coupling agent is selected as a combination of two or more, they can be in any ratio.
[0019] The surface resistance of the transparent antistatic protective film is 10 4 ~10 8 Ω, optical transmittance is 65% to 90%.
[0020] The method for preparing the transparent antistatic protective film specifically comprises the following steps:
[0021] (1) taking the pretreated substrate, coating the surface of the substrate with a polythiophene antistatic liquid, placing the substrate in an oven, and taking the substrate out after drying to obtain a substrate coated with a polythiophene antistatic layer;
[0022] (2) coating a silver-plated nanowire transparent antistatic functional coating on the polythiophene antistatic layer obtained in step (1), and placing the coating in an oven for drying to obtain a transparent antistatic protective film.
[0023] In the step (1), the pretreatment is specifically as follows: placing the substrate in a pretreatment solution for ultrasonic treatment for 15 to 60 minutes, rinsing the substrate after ultrasonic treatment with deionized water and then drying it, cleaning the surface of the dried substrate again by one or more of acid washing, alkaline washing, and oxygen plasma, then washing with deionized water, and drying to obtain a substrate with a completed surface treatment;
[0024] The pretreatment liquid is selected from one or more of acetone, isopropanol, anhydrous methanol, and anhydrous ethanol, and the purity is analytically pure. When multiple pretreatment liquids are selected, the multiple pretreatment liquids can be in any proportion.
[0025] The wet coating amount of the polythiophene antistatic liquid is 5 to 20 g / m 2 The oven temperature is 80-100°C and the drying time is 1-3 minutes.
[0026] In the step (2), when the polymer matrix of the silver-plated nanowire transparent antistatic functional coating is selected as a release agent, the wet coating amount is 0.1 to 1.5 g / m 2 ; When choosing pressure-sensitive adhesive, the wet coating amount is 30-50g / m 2 ; When selecting hardening resin, the wet coating amount is 10-30g / m 2 The oven temperature is 150-170°C and the drying time is 3-5 minutes.
[0027] In the step (1) and the step (2), the coating method is selected from one of micro-dimpled coating, wire rod coating, doctor blade coating, slit coating, spray coating, and roll-to-roll process.
[0028] The key points of the present invention are:
[0029] 1. Adding one-dimensional high aspect ratio silver-plated nanowires with excellent conductive properties as conductive fillers into the functional coating can form a good conductive network at a low filling amount (<3%), which greatly reduces the percolation threshold of the conductive filler while maintaining excellent antistatic function.
[0030] 2. The one-dimensional high aspect ratio silver-plated nanowires are chemically modified with a silane coupling agent, which improves the compatibility of the silver-plated nanowire conductive filler with the matrix and the dispersion stability in the matrix. The modified silver-plated nanowires have little effect on the functional coating, especially will not cause "poisoning" of the silicone pressure-sensitive adhesive of the platinum catalytic system or the silicone oil release agent of the platinum catalytic system, avoiding the problem of uncured or incompletely cured pressure-sensitive adhesive or release agent.
[0031] 3. A double-layer structure of polythiophene antistatic layer + silver-plated nanowire transparent antistatic functional layer is adopted. The synergistic effect of the double-layer structure improves the antistatic function of the film, while effectively avoiding the impact on the optical transmittance of the film; in addition, the silver-plated nanowire transparent antistatic functional layer also plays the role of isolating the air to protect the antistatic layer of the polythiophene system, solving the problem of unstable failure of the polythiophene antistatic layer in the air, greatly extending the service life of the transparent antistatic protective film, saving costs, and facilitating large-scale production.
[0032] Compared with the prior art, the present invention has the following beneficial effects:
[0033] 1. The preparation method of the transparent antistatic protective film provided by the present invention can effectively overcome the problems of low optical transmittance, unstable antistatic performance and non-curing or affected curing of the functional coating caused by adding conductive fillers in the functional coating of the existing transparent antistatic protective film.
[0034] 2. The method for preparing a transparent antistatic protective film of the present invention greatly reduces the amount of conductive filler added while ensuring the excellent optical transmittance of the film, and has excellent antistatic performance and high optical transparency.
[0035] 3. As the conductive filler of the functional coating in the transparent antistatic protective film of the present invention, the one-dimensional high aspect ratio silver-plated nanowires have abundant raw material sources, simple preparation process and short production cycle. In particular, the one-dimensional high aspect ratio silver-plated nanowires prepared by chemical plating process can effectively replace expensive metal nanowires. The process is green and environmentally friendly, with high raw material utilization rate. While ensuring excellent antistatic properties, it greatly reduces costs and is conducive to industrial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] Figure 1 Schematic diagram of the preparation principle of the transparent antistatic protective film of the present invention;
[0037] Figure 2 Schematic diagram of the structure of the transparent antistatic protective film of the present invention; wherein, 1-substrate layer, 2-polythiophene antistatic layer, 3-silver-plated nanowire transparent antistatic functional coating;
[0038] Figure 3 SEM images of the silver-plated tin dioxide nanowires and the transparent antistatic protective film prepared in Example 1 of the present invention; wherein, Figure (a) is the silver-plated tin dioxide nanowires, and Figure (b) is the transparent antistatic protective film. DETAILED DESCRIPTION
[0039] The following examples are provided for a better understanding of the present invention, are not limited to the best mode of implementation, and are not intended to limit the content and scope of the present invention. Any product identical or similar to the present invention obtained by combining the features of the present invention with other prior arts under the enlightenment of the present invention, falls within the protection scope of the present invention. If no specific experimental steps or conditions are indicated in the examples, the operation or conditions of the conventional experimental steps described in the literature in this area can be carried out. If the manufacturer is not indicated for the reagents or instruments used, they are all conventional reagent products that can be obtained commercially.
[0040] Example 1
[0041] A method for preparing a transparent antistatic protective film, the schematic diagram of its preparation principle is as follows Figure 1 As shown, the specific steps include:
[0042] (1) Substrate pretreatment:
[0043] PET with a thickness of 180 μm was used as a substrate, which was ultrasonically treated in a mixed solution of acetone and anhydrous ethanol for 15 minutes, with the volume ratio of acetone to anhydrous ethanol being 1:1. The substrate was then rinsed with deionized water and blown dry. The surface of the dried substrate was cleaned again with an oxygen plasma cleaner for 10 minutes, and finally washed with deionized water and dried to obtain a substrate with a surface treatment.
[0044] (2) Coating of polythiophene antistatic layer:
[0045] Take polythiophene and add it to a mixed solution of water and ethanol. The volume ratio of polythiophene, water and ethanol is 1:3:3. Stir for 30 minutes to disperse evenly. Spread the PET substrate flat on the operating table. Use the wire rod coating process to evenly drop the evenly dispersed polythiophene antistatic liquid on the upper edge of the PET substrate. The wet coating amount of the polythiophene antistatic liquid is 10g / m 2 The antistatic liquid was then scraped flat with a Meyer rod to form a film to obtain a polythiophene antistatic layer. The scraping speed of the Meyer rod was 50 mm / s. The coated PET substrate was placed in an oven at 80°C and dried for 2 min to obtain a substrate coated with a polythiophene antistatic layer. The thickness of the polythiophene antistatic layer was 1 μm and the surface resistance was 1.2×10 6 Ω.
[0046] (3) Silver-plated nanowire transparent antistatic functional coating:
[0047] Silver-plated tin dioxide nanowires with a diameter of 20 to 100 nm and a length of 10 to 50 μm are dispersed in a mixed solution of ethanol and cyclohexane, the volume ratio of ethanol to cyclohexane is 1:1, stirred for 30 minutes, uniformly dispersed, and obtained a silver-plated tin dioxide nanowire dispersion liquid, and then γ-methacryloxypropyltrimethoxysilane is added for chemical modification, stirred for 60 minutes, and the amount of silane coupling agent added is 0.3% of the total weight of the silver-plated tin dioxide nanowire dispersion liquid; then a silicone pressure-sensitive adhesive with a platinum catalytic system is added, and stirring is continued for 60 minutes, and ultrasonic dispersion is performed for 30 minutes to obtain a silver-plated tin dioxide nanowire antistatic liquid. Among them, the amount of the silver-plated tin dioxide nanowire dispersion liquid added is 20% of the total weight of the silicone pressure-sensitive adhesive, and the amount of the silver-plated tin dioxide nanowire added is 5% of the total weight of the silicone pressure-sensitive adhesive.
[0048] The substrate coated with the polythiophene antistatic layer was laid flat on the operating table, and the uniformly dispersed silver-plated tin dioxide nanowire antistatic liquid was evenly dropped on the upper edge of the substrate using a wire rod coating process, and then the silver-plated tin dioxide nanowire antistatic liquid was flatly scraped and coated into a film using a Meyer rod to obtain a silver-plated tin dioxide nanowire antistatic layer. The wet coating amount of the silver-plated tin dioxide nanowire antistatic liquid was 40g / m2 The coating speed of the Meyer rod is 20 mm / s; the coated substrate is placed in a 165°C oven and dried for 3 minutes to obtain a transparent antistatic protective film, the structural diagram of which is shown in FIG. Figure 2 As shown in the SEM images Figure 3 The thickness of the prepared silver-plated nanowire transparent antistatic functional coating is 10 μm and the surface resistance is 2.3×10 5 Ω, the thickness of the transparent antistatic protective film is 190μm.
[0049] Referring to GB / T 1410-2006, the surface resistance of the transparent antistatic protective film was tested by QUICK 499D surface resistance tester, and the optical transmittance of the transparent antistatic protective film was tested by UV-visible spectrophotometer. Each group was tested 20 times and the average value was calculated. The results are shown in Table 1.
[0050] Table 1 Properties of the transparent antistatic protective film obtained in Example 1
[0051]
[0052] Example 2
[0053] A method for preparing a transparent antistatic protective film comprises the following steps:
[0054] (1) Substrate pretreatment:
[0055] PET with a thickness of 180 μm was used as a substrate, which was ultrasonically treated in a mixed solution of acetone and anhydrous ethanol for 15 minutes, with the volume ratio of acetone to anhydrous ethanol being 1:1. The substrate was then rinsed with deionized water and blown dry. The surface of the dried substrate was cleaned again with an oxygen plasma cleaner for 10 minutes, and finally washed with deionized water and dried to obtain a substrate with a surface treatment.
[0056] (2) Coating of polythiophene antistatic layer:
[0057] Take polythiophene and add it to a mixed solution of water and ethanol. The volume ratio of polythiophene, water and ethanol is 1:3:3. Stir for 30 minutes to disperse evenly. Spread the PET substrate flat on the operating table. Use the wire rod coating process to evenly drop the evenly dispersed polythiophene antistatic liquid on the upper edge of the PET substrate. The wet coating amount of the polythiophene antistatic liquid is 10g / m 2 The antistatic liquid was then scraped flat with a Meyer rod to form a film to obtain a polythiophene antistatic layer. The scraping speed of the Meyer rod was 50 mm / s. The coated PET substrate was placed in an oven at 80°C and dried for 2 min to obtain a substrate coated with a polythiophene antistatic layer. The thickness of the polythiophene antistatic layer was 1.3 μm and the surface resistance was 1.5×10 6 Ω.
[0058] (3) Silver-plated nanowire transparent antistatic functional coating:
[0059] Silver-plated zinc oxide nanowires with a diameter of 10 to 50 nm and a length of 20 to 50 μm are dispersed in a mixed solution of ethyl acetate and cyclohexane, the volume ratio of ethyl acetate to cyclohexane is 1:1, stirred for 30 minutes, uniformly dispersed, and obtained a silver-plated zinc oxide nanowire dispersion liquid, and then γ-aminopropyltriethoxysilane is added for chemical modification, stirred for 60 minutes, and the amount of silane coupling agent added is 0.2% of the total weight of the silver-plated zinc oxide nanowire dispersion liquid; then a silicone pressure-sensitive adhesive with a platinum catalytic system is added, and stirring is continued for 60 minutes, and ultrasonic dispersion is performed for 30 minutes to obtain a silver-plated zinc oxide nanowire antistatic liquid. Among them, the amount of the silver-plated zinc oxide nanowire dispersion liquid added is 20% of the total weight of the silicone pressure-sensitive adhesive, and the amount of the silver-plated zinc oxide nanowire antistatic liquid added is 5% of the total weight of the silicone pressure-sensitive adhesive.
[0060] The substrate coated with the polythiophene antistatic layer was laid flat on the operating table, and the uniformly dispersed silver-coated zinc oxide nanowire antistatic liquid was evenly dropped on the upper edge of the substrate using a wire rod coating process, and then the silver-coated zinc oxide nanowire antistatic liquid was flatly scraped and coated into a film using a Meyer rod to obtain a silver-coated zinc oxide nanowire antistatic layer. The wet coating amount of the silver-coated zinc oxide nanowire antistatic liquid was 40g / m 2 The coating speed of the Meyer rod was 20 mm / s; the coated substrate was placed in an oven at 165°C for 3 min to obtain a transparent antistatic protective film. The thickness of the prepared silver-plated nanowire transparent antistatic functional coating was 12 μm and the surface resistance was 7.2×10 6 Ω, the thickness of the transparent antistatic protective film is 193μm.
[0061] Referring to GB / T 1410-2006, the surface resistance of the transparent antistatic protective film was tested by QUICK 499D surface resistance tester, and the optical transmittance of the transparent antistatic protective film was tested by UV-visible spectrophotometer. Each group was tested 20 times and the average value was calculated. The results are shown in Table 2.
[0062] Table 2 Performance of the transparent antistatic protective film obtained in Example 2
[0063]
[0064] Example 3
[0065] A method for preparing a transparent antistatic protective film comprises the following steps:
[0066] (1) Substrate pretreatment:
[0067] PET with a thickness of 180 μm was used as a substrate, which was ultrasonically treated in a mixed solution of acetone and anhydrous ethanol for 15 minutes, with the volume ratio of acetone to anhydrous ethanol being 1:1. The substrate was then rinsed with deionized water and blown dry. The surface of the dried substrate was cleaned again with an oxygen plasma cleaner for 10 minutes, and finally washed with deionized water and dried to obtain a substrate with a surface treatment.
[0068] (2) Coating of polythiophene antistatic layer:
[0069] Take polythiophene and add it to a mixed solution of water and ethanol. The volume ratio of polythiophene, water and ethanol is 1:3:3. Stir for 30 minutes to disperse evenly. Spread the PET substrate flat on the operating table. Use the wire rod coating process to evenly drop the evenly dispersed polythiophene antistatic liquid on the upper edge of the PET substrate. The wet coating amount of the polythiophene antistatic liquid is 10g / m 2 The antistatic liquid was then scraped flat with a Meyer rod to form a film to obtain a polythiophene antistatic layer. The scraping speed of the Meyer rod was 50 mm / s. The coated PET substrate was placed in an oven at 80°C and dried for 2 min to obtain a substrate coated with a polythiophene antistatic layer. The thickness of the polythiophene antistatic layer was 1.1 μm and the surface resistance was 1.8×10 6 Ω.
[0070] (3) Silver-plated nanowire transparent antistatic functional coating:
[0071] Silver-plated nickel nanowires with a diameter of 1 to 100 nm and a length of 0.5 to 100 μm are dispersed in a mixed solution of ethanol and isopropanol, the volume ratio of ethanol to isopropanol is 1:1, stirred for 30 minutes, uniformly dispersed, and a silver-plated nickel nanowire dispersion is obtained, and then γ-glycidoxypropylmethyldiethoxysilane is added for chemical modification, stirred for 60 minutes, and the amount of silane coupling agent added accounts for 0.3% of the total weight of the silver-plated nickel nanowire dispersion; then a silicone pressure-sensitive adhesive with a platinum catalytic system is added, and stirring is continued for 60 minutes, and ultrasonic dispersion is performed for 30 minutes to obtain a silver-plated nickel nanowire antistatic liquid. Among them, the amount of the silver-plated nickel nanowire dispersion added accounts for 10% of the total weight of the silicone pressure-sensitive adhesive, and the amount of the silver-plated nickel nanowire added accounts for 5% of the total weight of the silicone pressure-sensitive adhesive.
[0072] The substrate coated with the polythiophene antistatic layer was laid flat on the operating table, and the uniformly dispersed silver-plated nickel nanowire antistatic liquid was evenly dropped on the upper edge of the substrate using a wire rod coating process, and then the silver-plated nickel nanowire antistatic liquid was flatly scraped and coated into a film using a Meyer rod to obtain a silver-plated nickel nanowire antistatic layer. The wet coating amount of the silver-plated nickel nanowire antistatic liquid was 50g / m 2The coating speed of the Meyer rod was 20 mm / s; the coated substrate was placed in a 170°C oven and dried for 3 min to obtain a transparent antistatic protective film. The thickness of the prepared silver-plated nanowire transparent antistatic functional coating was 15 μm and the surface resistance was 2.4×10 7 Ω, the thickness of the transparent antistatic protective film is 195μm.
[0073] Referring to GB / T 1410-2006, the surface resistance of the transparent antistatic protective film was tested by QUICK 499D surface resistance tester, and the optical transmittance of the transparent antistatic protective film was tested by UV-visible spectrophotometer. Each group was tested 20 times and the average value was calculated. The results are shown in Table 3.
[0074] Table 3 Performance of the transparent antistatic protective film obtained in Example 3
[0075]
[0076] Example 4
[0077] A method for preparing a transparent antistatic protective film comprises the following steps:
[0078] (1) Substrate pretreatment:
[0079] PI with a thickness of 175 μm was used as the substrate, and was ultrasonically treated in a mixed solution of acetone and anhydrous ethanol for 15 minutes, with the volume ratio of acetone to anhydrous ethanol being 1:1. The substrate was then rinsed with deionized water and blown dry. The surface of the dried substrate was cleaned again with an oxygen plasma cleaner for 10 minutes, and finally washed with deionized water and dried to obtain a substrate with a surface treatment.
[0080] (2) Coating of polythiophene antistatic layer:
[0081] Take polythiophene and add it to a mixed solution of water and ethanol. The volume ratio of polythiophene, water and ethanol is 1:3:3. Stir for 30 minutes to disperse evenly. Spread the PI substrate flat on the operating table. Use the wire rod coating process to evenly drop the evenly dispersed polythiophene antistatic liquid on the upper edge of the PI substrate. The wet coating amount of the polythiophene antistatic liquid is 10g / m 2 The antistatic liquid was then scraped flat with a Meyer rod to form a film to obtain a polythiophene antistatic layer. The scraping speed of the Meyer rod was 50 mm / s. The coated PI substrate was placed in an oven at 80°C and dried for 2 min to obtain a substrate coated with a polythiophene antistatic layer. The thickness of the polythiophene antistatic layer was 1.7 μm and the surface resistance was 4.2×10 6 Ω.
[0082] (3) Silver-plated nanowire transparent antistatic functional coating:
[0083] Silver-plated carbon nanotubes with a diameter of 5 to 20 nm and a length of 5 to 50 μm are dispersed in a mixed solution of ethanol and isopropanol, the volume ratio of ethanol to isopropanol is 1:1, stirred for 60 minutes, uniformly dispersed, and a silver-plated carbon nanotube dispersion is obtained, and then γ-glycidoxypropyltrimethoxysilane is added for chemical modification, stirred for 120 minutes, and the amount of silane coupling agent added accounts for 0.5% of the total weight of the silver-plated carbon nanotube dispersion; then a silicone pressure-sensitive adhesive with a platinum catalytic system is added, and stirring is continued for 60 minutes, and ultrasonic dispersion is performed for 60 minutes to obtain a silver-plated carbon nanotube antistatic liquid. Among them, the amount of the silver-plated carbon nanotube dispersion added accounts for 20% of the total weight of the silicone pressure-sensitive adhesive, and the amount of the silver-plated carbon nanotube added accounts for 5% of the total weight of the silicone pressure-sensitive adhesive.
[0084] The substrate coated with the polythiophene antistatic layer was laid flat on the operating table, and the uniformly dispersed silver-coated carbon nanotube antistatic liquid was evenly dropped on the upper edge of the substrate using a wire rod coating process, and then the silver-coated carbon nanotube antistatic liquid was flatly scraped and coated into a film using a Meyer rod to obtain a silver-coated carbon nanotube antistatic layer. The wet coating amount of the silver-coated carbon nanotube antistatic liquid was 40g / m 2 The coating speed of the Meyer rod was 20 mm / s; the coated substrate was placed in a 170°C oven and dried for 2 min to obtain a transparent antistatic protective film. The thickness of the prepared silver-plated nanowire transparent antistatic functional coating was 18 μm and the surface resistance was 3.3×10 5 Ω, the thickness of the transparent antistatic protective film is 196μm.
[0085] Referring to GB / T 1410-2006, the surface resistance of the transparent antistatic protective film was tested by QUICK 499D surface resistance tester, and the optical transmittance of the transparent antistatic protective film was tested by UV-visible spectrophotometer. Each group was tested 20 times and the average value was calculated. The results are shown in Table 4.
[0086] Table 4 Performance of the transparent antistatic protective film obtained in Example 4
[0087]
[0088] Example 5
[0089] A method for preparing a transparent antistatic protective film comprises the following steps:
[0090] (1) Substrate pretreatment:
[0091] PI with a thickness of 175 μm was used as the substrate, and was ultrasonically treated in a mixed solution of acetone and anhydrous ethanol for 15 minutes, with the volume ratio of acetone to anhydrous ethanol being 1:1. The substrate was then rinsed with deionized water and blown dry. The surface of the dried substrate was cleaned again with an oxygen plasma cleaner for 10 minutes, and finally washed with deionized water and dried to obtain a substrate with a surface treatment.
[0092] (2) Coating of polythiophene antistatic layer:
[0093] Take polythiophene and add it to a mixed solution of water and ethanol. The volume ratio of polythiophene, water and ethanol is 1:3:3. Stir for 30 minutes to disperse evenly. Spread the PI substrate flat on the operating table. Use the wire rod coating process to evenly drop the evenly dispersed polythiophene antistatic liquid on the upper edge of the PI substrate. The wet coating amount of the polythiophene antistatic liquid is 10g / m 2 The antistatic liquid was then scraped flat with a Meyer rod to form a film to obtain a polythiophene antistatic layer. The scraping speed of the Meyer rod was 50 mm / s. The coated PI substrate was placed in an oven at 80°C and dried for 2 min to obtain a substrate coated with a polythiophene antistatic layer. The thickness of the polythiophene antistatic layer was 1.4 μm and the surface resistance was 1.6×10 6 Ω.
[0094] (3) Silver-plated nanowire transparent antistatic functional coating:
[0095] Silver-plated tin dioxide nanowires with a diameter of 20 to 100 nm and a length of 10 to 50 μm are dispersed in a mixed solution of ethyl acetate and cyclohexane, the volume ratio of ethyl acetate to cyclohexane is 1:1, stirred for 30 minutes, uniformly dispersed, and obtained a silver-plated tin dioxide nanowire dispersion liquid, and then γ-methacryloxypropyltrimethoxysilane is added for chemical modification, stirred for 60 minutes, and the amount of silane coupling agent added is 0.3% of the total weight of the silver-plated tin dioxide nanowire dispersion liquid; then polyurethane resin is added, stirred for 30 minutes, and ultrasonically dispersed for 30 minutes to obtain a silver-plated tin dioxide nanowire antistatic liquid. Among them, the amount of silver-plated tin dioxide nanowire dispersion liquid added is 10% of the total weight of the polyurethane resin, and the silver-plated tin dioxide nanowire is 5% of the total weight of the polyurethane resin.
[0096] The substrate coated with the polythiophene antistatic layer was laid flat on the operating table, and the uniformly dispersed silver-plated tin dioxide nanowire antistatic liquid was evenly dropped on the upper edge of the substrate using a wire rod coating process, and then the silver-plated tin dioxide nanowire antistatic liquid was flatly scraped and coated into a film using a Meyer rod to obtain a silver-plated tin dioxide nanowire antistatic layer. The wet coating amount of the silver-plated tin dioxide nanowire antistatic liquid was 20g / m 2The coating speed of the Meyer rod was 10 mm / s; the coated substrate was placed in a 150°C oven and dried for 2 min to obtain a transparent antistatic protective film. The thickness of the prepared silver-plated nanowire transparent antistatic functional coating was 8 μm and the surface resistance was 6.7×10 5 Ω, the thickness of the transparent antistatic protective film is 185μm.
[0097] Referring to GB / T 1410-2006, the surface resistance of the transparent antistatic protective film was tested by QUICK 499D surface resistance tester, and the optical transmittance of the transparent antistatic protective film was tested by UV-visible spectrophotometer. Each group was tested 20 times and the average value was calculated. The results are shown in Table 5.
[0098] Table 5 Properties of the transparent antistatic protective film obtained in Example 5
[0099]
[0100] Example 6
[0101] A method for preparing a transparent antistatic protective film comprises the following steps:
[0102] (1) Substrate pretreatment:
[0103] PET with a thickness of 180 μm was used as a substrate, which was ultrasonically treated in a mixed solution of acetone and anhydrous ethanol for 15 minutes, with the volume ratio of acetone to anhydrous ethanol being 1:1. The substrate was then rinsed with deionized water and blown dry. The surface of the dried substrate was cleaned again with an oxygen plasma cleaner for 10 minutes, and finally washed with deionized water and dried to obtain a substrate with a surface treatment.
[0104] (2) Coating of polythiophene antistatic layer:
[0105] Take polythiophene and add it to a mixed solution of water and ethanol. The volume ratio of polythiophene, water and ethanol is 1:3:3. Stir for 30 minutes to disperse evenly. Spread the PET substrate flat on the operating table and use a scraper coating process to evenly drop the evenly dispersed polythiophene antistatic liquid on the upper edge of the PET substrate. The wet coating amount of the polythiophene antistatic liquid is 20g / m 2 The antistatic liquid was then scraped flatly with a scraper to form a film to obtain a polythiophene antistatic layer. The scraping speed of the scraper was 30 mm / s. The coated PET substrate was placed in an oven at 80°C and dried for 2 min to obtain a substrate coated with a polythiophene antistatic layer. The thickness of the polythiophene antistatic layer was 1.3 μm and the surface resistance was 2.9×10 6 Ω.
[0106] (3) Silver-plated nanowire transparent antistatic functional coating:
[0107] Silver-plated zinc oxide nanowires with a diameter of 10 to 50 μm and a length of 20 to 50 μm are dispersed in a mixed solution of ethyl acetate and cyclohexane, the volume ratio of ethyl acetate to cyclohexane is 1:1, stirred for 30 minutes, uniformly dispersed, and obtained a silver-plated zinc oxide nanowire dispersion liquid, and then γ-aminopropyltriethoxysilane is added for chemical modification, stirred for 60 minutes, and the amount of silane coupling agent added is 0.2% of the total weight of the silver-plated zinc oxide nanowire dispersion liquid; then a silicone pressure-sensitive adhesive with a platinum catalytic system is added, and stirring is continued for 60 minutes, and ultrasonic dispersion is performed for 30 minutes to obtain a silver-plated zinc oxide nanowire antistatic liquid. Among them, the amount of the silver-plated zinc oxide nanowire dispersion liquid added is 5% of the total weight of the silicone pressure-sensitive adhesive, and the silver-plated zinc oxide nanowires are 5% of the total weight of the silicone pressure-sensitive adhesive.
[0108] The substrate coated with the polythiophene antistatic layer was laid flat on the operating table, and the uniformly dispersed silver-plated zinc oxide nanowire antistatic liquid was evenly dropped on the upper edge of the substrate by a scraper coating process, and then the silver-plated zinc oxide nanowire antistatic liquid was flatly scraped and coated with a scraper to form a film to obtain a silver-plated zinc oxide nanowire antistatic layer. The wet coating amount of the silver-plated zinc oxide nanowire antistatic liquid was 50g / m 2 The scraping speed of the scraper is 10 mm / s; the coated substrate is placed in a 165°C oven and dried for 3 minutes to obtain a transparent antistatic protective film. The thickness of the prepared silver-plated nanowire transparent antistatic functional coating is 17 μm, and the surface resistance is 8.1×10 6 Ω, the thickness of the transparent antistatic protective film is 198μm.
[0109] Referring to GB / T 1410-2006, the surface resistance of the transparent antistatic protective film was tested by QUICK 499D surface resistance tester, and the optical transmittance of the transparent antistatic protective film was tested by UV-visible spectrophotometer. Each group was tested 20 times and the average value was calculated. The results are shown in Table 6.
[0110] Table 6 Properties of the transparent antistatic protective film obtained in Example 6
[0111]
[0112] Example 7
[0113] A method for preparing a transparent antistatic protective film comprises the following steps:
[0114] (1) Substrate pretreatment:
[0115] PET with a thickness of 180 μm was used as a substrate, which was ultrasonically treated in a mixed solution of acetone and anhydrous ethanol for 15 minutes, with the volume ratio of acetone to anhydrous ethanol being 1:1. The substrate was then rinsed with deionized water and blown dry. The surface of the dried substrate was cleaned again with an oxygen plasma cleaner for 10 minutes, and finally washed with deionized water and dried to obtain a substrate with a surface treatment.
[0116] (2) Coating of polythiophene antistatic layer:
[0117] Take polythiophene and add it to a mixed solution of water and ethanol. The volume ratio of polythiophene, water and ethanol is 1:3:3. Stir for 30 minutes to disperse evenly. Spread the PET substrate flat on the operating table and use a scraper coating process to evenly drop the evenly dispersed polythiophene antistatic liquid on the upper edge of the PET substrate. The wet coating amount of the polythiophene antistatic liquid is 20g / m 2 The antistatic liquid was then scraped flatly with a scraper to form a film to obtain a polythiophene antistatic layer. The scraping speed of the scraper was 30 mm / s. The coated PET substrate was placed in an oven at 80°C and dried for 2 min to obtain a substrate coated with a polythiophene antistatic layer. The thickness of the polythiophene antistatic layer was 1.5 μm and the surface resistance was 1.9×10 6 Ω.
[0118] (3) Silver-plated nanowire transparent antistatic functional coating:
[0119] Silver-plated nickel nanowires with a diameter of 1 to 100 nm and a length of 0.5 to 100 μm are dispersed in a mixed solution of ethanol and isopropanol, the volume ratio of ethanol to isopropanol is 1:1, stirred for 30 minutes, uniformly dispersed, and a silver-plated nickel nanowire dispersion is obtained, and then γ-glycidoxypropylmethyldiethoxysilane is added for chemical modification, stirred for 60 minutes, and the amount of silane coupling agent added accounts for 0.3% of the total weight of the silver-plated nickel nanowire dispersion; then polyurethane resin is added, stirred for 60 minutes, and ultrasonically dispersed for 30 minutes to obtain a silver-plated nickel nanowire antistatic liquid. Among them, the amount of silver-plated nickel nanowire dispersion accounts for 10% of the total weight of the polyurethane resin, and the silver-plated nickel nanowire is 5% of the total weight of the silicone pressure-sensitive adhesive of the platinum catalysis system.
[0120] The substrate coated with the polythiophene antistatic layer was laid flat on the operating table, and the uniformly dispersed silver-plated nickel nanowire antistatic liquid was evenly dropped on the upper edge of the substrate by a scraper coating process, and then the silver-plated nickel nanowire antistatic liquid was flatly scraped and coated with a scraper to form a film to obtain a silver-plated nickel nanowire antistatic layer. The wet coating amount of the silver-plated nickel nanowire antistatic liquid was 20g / m 2The scraping speed of the scraper is 10 mm / s; the coated substrate is placed in a 150°C oven and dried for 2 minutes to obtain a transparent antistatic protective film. The thickness of the prepared silver-plated nanowire transparent antistatic functional coating is 13 μm, and the surface resistance is 5.7×10 7 Ω, the thickness of the transparent antistatic protective film is 195μm.
[0121] Referring to GB / T 1410-2006, the surface resistance of the transparent antistatic protective film was tested by QUICK 499D surface resistance tester, and the optical transmittance of the transparent antistatic protective film was tested by UV-visible spectrophotometer. Each group was tested 20 times and the average value was calculated. The results are shown in Table 7.
[0122]
[0123]
[0124] Example 8
[0125] A method for preparing a transparent antistatic protective film comprises the following steps:
[0126] (1) Substrate pretreatment:
[0127] PI with a thickness of 175 μm was used as the substrate, and was ultrasonically treated in a mixed solution of acetone and anhydrous ethanol for 15 minutes, with the volume ratio of acetone to anhydrous ethanol being 1:1. The substrate was then rinsed with deionized water and blown dry. The surface of the dried substrate was cleaned again with an oxygen plasma cleaner for 10 minutes, and finally washed with deionized water and dried to obtain a substrate with a surface treatment.
[0128] (2) Coating of polythiophene antistatic layer:
[0129] Take polythiophene and add it to a mixed solution of water and ethanol. The volume ratio of polythiophene, water and ethanol is 1:3:3. Stir for 30 minutes to disperse evenly. Spread the PI substrate flat on the operating table and use a scraper coating process to evenly drop the evenly dispersed polythiophene antistatic liquid on the upper edge of the PI substrate. The wet coating amount of the polythiophene antistatic liquid is 20g / m 2 The antistatic liquid was then scraped flatly with a scraper to form a film to obtain a polythiophene antistatic layer. The scraping speed of the scraper was 30 mm / s. The coated PI substrate was placed in an oven at 80 °C and dried for 2 min to obtain a substrate coated with a polythiophene antistatic layer. The thickness of the polythiophene antistatic layer was 1.8 μm and the surface resistance was 2.3×10 6 Ω.
[0130] (3) Silver-plated nanowire transparent antistatic functional coating:
[0131] Silver-plated carbon nanotubes with a diameter of 5 to 20 nm and a length of 5 to 50 μm are dispersed in a mixed solution of ethanol and isopropanol, the volume ratio of ethanol to isopropanol is 1:1, stirred for 60 minutes, uniformly dispersed, and a silver-plated carbon nanotube dispersion is obtained, and then γ-glycidoxypropyltrimethoxysilane is added for chemical modification, stirred for 120 minutes, and the amount of silane coupling agent added accounts for 0.5% of the total weight of the silver-plated carbon nanotube dispersion; then polyurethane resin is added, stirred for 60 minutes, and ultrasonically dispersed for 60 minutes to obtain a silver-plated carbon nanotube antistatic liquid. Among them, the amount of silver-plated carbon nanotube dispersion added accounts for 5% of the total weight of the polyurethane resin, and the silver-plated carbon nanotube is 5% of the total weight of the silicone pressure-sensitive adhesive of the platinum catalysis system.
[0132] The substrate coated with the polythiophene antistatic layer was laid flat on the operating table, and the uniformly dispersed silver-plated carbon nanotube antistatic liquid was evenly dropped on the upper edge of the substrate by a scraper coating process, and then the silver-plated carbon nanotube antistatic liquid was scraped flatly with a scraper to form a film to obtain a silver-plated nickel nanowire antistatic layer. The wet coating amount of the silver-plated carbon nanotube antistatic liquid was 20g / m 2 The scraping speed of the scraper is 10 mm / s; the coated substrate is placed in a 150°C oven and dried for 2 minutes to obtain a transparent antistatic protective film. The thickness of the prepared silver-plated nanowire transparent antistatic functional coating is 15 μm, and the surface resistance is 4.5×10 5 Ω, the thickness of the transparent antistatic protective film is 192μm.
[0133] Referring to GB / T 1410-2006, the surface resistance of the transparent antistatic protective film was tested by QUICK 499D surface resistance tester, and the optical transmittance of the transparent antistatic protective film was tested by UV-visible spectrophotometer. Each group was tested 20 times and the average value was calculated. The results are shown in Table 8.
[0134]
Claims
1. A transparent antistatic protective film, characterized in that: Specifically comprising a substrate and a coating attached thereto, wherein the coating comprises a polythiophene antistatic layer and a silver-plated nanowire transparent antistatic functional coating; A polythiophene antistatic layer and a silver-plated nanowire transparent antistatic functional coating are sequentially arranged on one surface of the substrate; The thickness of the transparent antistatic protective film is 50 to 200 μm, the thickness of the substrate is 10 to 200 μm; the surface resistance of the polythiophene antistatic layer is 10 5 ~10 7 Ω, thickness is 0.05~50μm; the surface resistance of the silver-plated nanowire transparent antistatic functional coating is 10 4 ~10 8 Ω, thickness is 0.1~100μm.
2. A transparent antistatic protective film according to claim 1, characterized in that: The material of the substrate is selected from one of PET, PI, PE, PP, and PVC films; the polythiophene antistatic layer is prepared by coating a polythiophene antistatic liquid on the surface of the substrate; and the silver-plated nanowire transparent antistatic functional coating is prepared by mixing a silver-plated nanowire dispersion with a polymer matrix and ultrasonically dispersing the mixture, and then coating the mixture on the surface of the polythiophene antistatic layer.
3. A transparent antistatic protective film according to claim 2, characterized in that: The preparation method of the polythiophene antistatic liquid is as follows: adding polythiophene to a mixed solution of ethanol and water, and stirring the mixture to obtain the antistatic liquid; wherein the volume ratio of polythiophene to ethanol and water is 1:(1-3):(1-3), and the polythiophene and ethanol are analytically pure; The polymer matrix is selected from one of a release agent, a pressure-sensitive adhesive and a hardening resin, wherein the release agent is a silicone oil release agent, the pressure-sensitive adhesive is selected from one of an organic silicone pressure-sensitive adhesive, an acrylate pressure-sensitive adhesive and a rubber pressure-sensitive adhesive, and the hardening resin is selected from one of an acrylic resin, a polyurethane resin and an epoxy resin; The silicone oil release agent is a silicone oil release agent of a platinum catalytic system, and the pressure-sensitive adhesive is an organic silicone pressure-sensitive adhesive of a platinum catalytic system; The preparation method of the silver-plated nanowire dispersion is as follows: adding the silver-plated nanowires into an organic solvent, adding a silane coupling agent for modification, and stirring to obtain the dispersion; The addition amount of the silver-plated nanowire dispersion accounts for 1% to 20% of the total weight of the polymer matrix, the addition amount of the silver-plated nanowires accounts for 0.5% to 10.0% of the total weight of the polymer matrix, and the addition amount of the silane coupling agent accounts for 0.1% to 0.5% of the total weight of the silver-plated nanowire dispersion.
4. A transparent antistatic protective film according to claim 3, characterized in that: The silver-plated nanowires are specifically one-dimensional high aspect ratio silver-plated nanowires, selected from one or more of silver-plated nickel nanowires, silver-plated carbon nanotubes, silver-plated tin dioxide nanowires, and silver-plated zinc oxide nanowires, all of which are prepared by chemical plating process. When multiple types of silver-plated nanowires are selected, the multiple types are in any proportion. The silver-plated nickel nanowire has a diameter of 1 to 100 nm and a length of 0.5 to 100 μm, the silver-plated carbon nanotube has a diameter of 5 to 20 nm and a length of 5 to 50 μm, the silver-plated tin dioxide nanowire has a diameter of 20 to 100 nm and a length of 10 to 50 μm, and the silver-plated zinc oxide nanowire has a diameter of 10 to 50 μm and a length of 20 to 50 μm; The organic solvent is selected from at least two of ethanol, isopropanol, ethyl acetate and cyclohexane, and the organic solvents are in any proportion. The purity of the organic solvent is analytical grade.
5. The transparent antistatic protective film according to claim 3, characterized in that: The silane coupling agent is selected from one or a combination of two or more of γ-glycidoxypropyltrimethoxysilane, γ-glycidoxypropylmethyldiethoxysilane, N-(2-aminoethyl-3-aminopropyl)methyldimethoxysilane, n-octyltriethoxysilane, γ-aminopropyltriethoxysilane, γ-methacryloxypropyltrimethoxysilane, 3-glycidyloxypropyltrimethoxysilane, N-β (aminoethyl)γ-aminopropyltrimethoxysilane and N-β (aminoethyl)γ-aminopropylmethyldimethoxysilane, and the purity of the silane coupling agent is analytically pure; when the silane coupling agent is selected as a combination of two or more, they can be in any ratio.
6. The transparent antistatic protective film according to claim 1, characterized in that: The surface resistance of the transparent antistatic protective film is 10 4 ~10 8 Ω, optical transmittance is 65% to 90%.
7. The method for preparing a transparent antistatic protective film according to claim 1, characterized in that: The specific steps include: (1) taking the pretreated substrate, coating the surface of the substrate with a polythiophene antistatic liquid, placing the substrate in an oven, and taking the substrate out after drying to obtain a substrate coated with a polythiophene antistatic layer; (2) coating a silver-plated nanowire transparent antistatic functional coating on the polythiophene antistatic layer obtained in step (1), and placing the coating in an oven for drying to obtain a transparent antistatic protective film.
8. The method for preparing a transparent antistatic protective film according to claim 7, characterized in that: In the step (1), the pretreatment is specifically as follows: placing the substrate in a pretreatment solution for ultrasonic treatment for 15 to 60 minutes, rinsing the substrate after ultrasonic treatment with deionized water and then drying it, cleaning the surface of the dried substrate again by one or more of acid washing, alkaline washing, and oxygen plasma, then washing with deionized water, and drying to obtain a substrate with a completed surface treatment; The pretreatment liquid is selected from one or more of acetone, isopropanol, anhydrous methanol, and anhydrous ethanol, and the purity is analytically pure. When multiple pretreatment liquids are selected, the multiple pretreatment liquids can be in any proportion. The wet coating amount of the polythiophene antistatic liquid is 5 to 20 g / m 2 The oven temperature is 80-100°C and the drying time is 1-3 minutes.
9. The method for preparing a transparent antistatic protective film according to claim 7, characterized in that: In the step (2), when the polymer matrix of the silver-plated nanowire transparent antistatic functional coating is selected as a release agent, the wet coating amount is 0.1 to 1.5 g / m 2 ; When choosing pressure-sensitive adhesive, the wet coating amount is 30-50g / m 2 ; When selecting hardening resin, the wet coating amount is 10-30g / m 2 The oven temperature is 150-170°C and the drying time is 3-5 minutes.
10. The method for preparing a transparent antistatic protective film according to claim 7, characterized in that: In the step (1) and the step (2), the coating method is selected from one of micro-dimpled coating, wire rod coating, doctor blade coating, slit coating, spray coating, and roll-to-roll process.
Citation Information
Patent Citations
An antistatic, highly transparent polyethylene film for packaging and its preparation method
CN114773717B
Cited By
Long-acting anti-static PE packaging film material and preparation method thereof
CN122060240A
